TEACHERS' PEDAGOGICAL COMPETENCE IN THE LEARNING PROCESS OF ISLAMIC RELIGIOUS EDUCATION AT MUHAMMADIYAH 02 PRIVATE SENIOR HIGH SCHOOL MEDAN - Abrianto, Danny; Tumiran, Tumiran; Rangkuti, Charles; Umat, Hardakwah (Sekolah Tinggi Agama Islam Al Hidayah, 2024)
Education is a complex system, where education is not only about students but also about the learning process, media, and teachers. Teachers are a crucial component of education because they are responsible for designing the learning process so that lessons can be effectively received by students. Therefore, teachers are required to possess competencies that support their performance. This study aims to explore the pedagogical competence of teachers in the Islamic religious education learning process at Muhammadiyah Private High School 02 Medan. The focus of this research includes: (1) How is the pedagogical competence of Islamic Religious Education (IRE) teachers in the learning process at Muhammadiyah Private High School 02 Medan, (2) How is the IRE learning process at Muhammadiyah Private High School 02 Medan, (3) What are the obstacles faced by IRE teachers in the learning process at Muhammadiyah Private High School 02 Medan. This research is a qualitative study. The data and findings obtained were processed and described based on the author's narrative. The data sources were primary sources, namely the Principal, IRE teachers, and students, as well as secondary sources obtained from documents and photographs related to Muhammadiyah Private High School 02 Medan. The researcher acted as a participant. Data collection procedures included observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results of the study show that the pedagogical competence of Islamic Religious Education teachers at Muhammadiyah Private High School 02 Medan is considered fairly good. Teachers are able to understand student characteristics, design learning materials, and manage the classroom effectively. The IRE learning process is carried out interactively with varied approaches such as lectures, discussions, and question-and-answer sessions, although there are still some limitations in utilizing innovative learning media. The obstacles faced by IRE teachers include a lack of supporting facilities and infrastructure, uneven student learning motivation, and limited time to cover material comprehensively. Nevertheless, teachers continue to strive to improve the quality of learning through reflection and independent competency development